Магнитное поле линий электропередачи и методы его снижения до безопасного уровня - Розов, В.Ю.; Реуцкий, С.Ю.; Пелевин, Д.Е.; Пилюгина, О.Ю. (Технічна електродинаміка, 2012)
The mathematical model of the magnetic field (MF) of the power transmission line (PTL) which is based on the multidipole representation is suggested. It permits of modeling MF in the vicinity of the boundary of protection zone of PTL taking into account the real configuration of wires. The model contains dipole sources which are characterized by the magnetic moments of the independent micro-contours d􀁵a. The current contours formed by wires of different phases of PTL with interphase spacing d are divided into the set of such micro-contours. The MP at the observation point is defined as the sum of MPs from the magnetic moments of all micro-contours. The method of mitigation of MP of PTL, which is based on the optimization of the spatial topology of the phase conductors splitting is suggested. This method permits to achieve the axial symmetry of the system of maximum order. In this way the method reduces the dipole component of the MP, increases the order of spatial harmonic of the main system, which determines the intensity of damping MP. As a result, it reduces the power line magnetic field to a safe level.